Experimental ion mobility measurements in Xe-C2H6. (19th October 2017) - Perdigoto, J.M.C.; Cortez, A.F.V.; Veenhof, R.; Neves, P.N.B.; Santos, F.P.; Borges, F.I.G.M.; Conde, C.A.N.
Abstract: In this paper we present the results of the ion mobility measurements made in gaseous mixtures of xenon (Xe) with ethane (C2 H6 ) for pressures ranging from 6 to 10 Torr (8–10.6 mbar) and for low reduced electric fields in the 10 Td to 25 Td range (2.4–6.1 kV⋅cm −1 ⋅ bar −1 ), at room temperature. The time of arrival spectra revealed two peaks throughout the entire range studied which were attributed to ion species with 3-carbons (C3 H5 +, C3 H6 + C3 H8 + and C3 H9 + ) and with 4-carbons (C4 H7 +, C4 H9 + and C4 H10 + ). Besides these, and for Xe concentrations above 70%, a bump starts to appear at the right side of the main peak for reduced electric fields higher than 20 Td, which was attributed to the resonant charge transfer of C2 H6 + to C2 H6 that affects the mobility of its ion products (C3 H8 + and C3 H9 + ). The time of arrival spectra for Xe concentrations of 20%, 50%, 70% and 90% are presented, together with the reduced mobilities as a function of the Xe concentration calculated from the peaks observed for the low reduced electric fields and pressures studied.